Facile green synthesis of ZnO–CdWO4 nanoparticles and their potential as adsorbents to remove organic dye. (15th February 2021) - Fatima, Bushra; Siddiqui, Sharf Ilahi; Nirala, Ranjeet Kumar; Vikrant, Kumar; Kim, Ki-Hyun; Ahmad, Rabia; Chaudhry, Saif Ali
Abstract: In this work, ZnO–CdWO4 nanoparticles have been synthesized by the ecofriendly green method with lemon leaf extract to favorably anchor functional groups on their surface. The prepared ZnO–CdWO4 nanoparticles are used as adsorbent to treat Congo red (CR) dye after characterization through FT-IR, UV–Vis, TEM, SEM-EDX, and HRTEM techniques. The equilibrium partition coefficient and adsorption capacity values for CR by ZnO–CdWO4 are estimated as 21.4 mg g −1 μM −1 and 5 mg g −1, respectively (at an initial dye concentration of 10 mg L −1 ). The adsorption process is found as exothermic and spontaneous, as determined by the ΔG°, ΔS°, and ΔH° values. The Boyd plot has been used as a confirmatory tool to fit the adsorption kinetics data along with intraparticle diffusion and pseudo-second-order models. Based on this research, ZnO–CdWO4 nanoparticles are validated as an effective adsorbent for CR dye in aqueous solutions. Graphical abstract: Image 1 Highlights: ZnO–CdWO4 was prepared using the Lemon leaf extract for CR adsorption application. The diameters of ZnO–CdWO4 particles were in the range between 10 and 40 nm. The adsorption process was exothermic and spontaneous with the capacity of 5 mg g −1 . The partition coefficient of CR by ZnO–CdWO4 was estimated as 21.4 mg g −1 μM −1 .